2018
DOI: 10.1186/s12936-018-2620-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of molecular markers of sulfadoxine–pyrimethamine and artemisinin resistance in Plasmodium falciparum from Pakistan

Abstract: BackgroundIn Pakistan, artesunate (AS) in combination with sulfadoxine–pyrimethamine (SP) is the recommended treatment for uncomplicated Plasmodium falciparum malaria. Monitoring molecular markers of anti-malarial drug resistance is crucial for early detection and containment of parasite resistance to treatment. Currently, no data are available on molecular markers of artemisinin resistance (K13 mutations) in P. falciparum isolates from Pakistan. In this study, the prevalence of mutations associated with SP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
3
17
2
Order By: Relevance
“…Other studies have found that all three types are present in India [54,55], whereas Indonesia, Thailand and South Korea have only Type 1 and Type 2 [7,52]. The role of the tandem repeat variants in SP resistance remains unclear [7,56] as these variants are not present in the Pfdhfr gene in P. falciparum [26,57]. However, Type 3 variants were exclusively linked to the L/I57:R58:M61:T117 mutations, which are associated with pyrimethamine resistance in P. vivax.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that all three types are present in India [54,55], whereas Indonesia, Thailand and South Korea have only Type 1 and Type 2 [7,52]. The role of the tandem repeat variants in SP resistance remains unclear [7,56] as these variants are not present in the Pfdhfr gene in P. falciparum [26,57]. However, Type 3 variants were exclusively linked to the L/I57:R58:M61:T117 mutations, which are associated with pyrimethamine resistance in P. vivax.…”
Section: Discussionmentioning
confidence: 99%
“…Due to spreading chloroquine resistance most of the remainder of India adopted ASP as first-line treatment by 2012. ASP is similarly recommended in neighbouring Pakistan [5]. There is thus considerable regional artemisinin and SP drug pressure and consequently a high risk of resistance spreading further.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, five non-synonymous mutations P615L, A578S, I543V, A676S and C580Y were identified in the Kelch 13 gene. The P615L mutation was detected in Pakistan [33]. Also, A676S has been identified in Africa and South-East Asia [34].…”
Section: Discussionmentioning
confidence: 97%